2005
DOI: 10.1186/1475-2875-4-52
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of KO-Tab 1-2-3®: a wash-resistant 'dip-it-yourself' insecticide formulation for long-lasting treatment of mosquito nets

Abstract: Introduction: Insecticide-treated nets (ITN) are an important method of preventing malaria. To remain effective, they need to be re-treated with pyrethroid insecticide at approximately yearly intervals. Systems for re-treating nets in Africa are limited, and the vast majority of nets in use have never been treated or were treated only once. Bayer Environmental Science (BES) has developed a long-lasting formulation 'KO-Tab 1-2-3 ® ' which can be applied to the net post-manufacture, under field conditions, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 9 publications
1
19
0
1
Order By: Relevance
“…LLINs from this campaign had just exceeded the three-year mark by the end of the trap evaluation, and thus, were counted as untreated. Furthermore, while large numbers of untreated nets had been distributed by KEMRI\CDC in the Asembo Bay area of Rarieda, these nets were treated with the KO-Tab 123 (a long-lasting insecticide formulation) [39] in early 2007. Therefore, it is likely that many of the bed nets used during this study still exhibited insecticidal activity, but were reported as untreated to err on the side of caution.…”
Section: Resultsmentioning
confidence: 99%
“…LLINs from this campaign had just exceeded the three-year mark by the end of the trap evaluation, and thus, were counted as untreated. Furthermore, while large numbers of untreated nets had been distributed by KEMRI\CDC in the Asembo Bay area of Rarieda, these nets were treated with the KO-Tab 123 (a long-lasting insecticide formulation) [39] in early 2007. Therefore, it is likely that many of the bed nets used during this study still exhibited insecticidal activity, but were reported as untreated to err on the side of caution.…”
Section: Resultsmentioning
confidence: 99%
“…Alpha-cypermethrin content of unwashed and washed nets was determined from net samples measuring 5 cm × 5 cm using the method described by Yates et al [11]. Alpha-cypermethrin was extracted using acetonitrile and injected onto HPLC (Dionex Summit, Camberly, Surrey, UK), separated on a 120Å column, eluted with a 9:1 solution of water:acetonitrile and passed through a PDA-100 detector at 275 nm.…”
Section: Methodsmentioning
confidence: 99%
“…There is a growing awareness of the potential environmental impact of the increasing number of used and discarded ITNs. 4,5 As it is widely recognised that ITNs lose their effectiveness with time, [4][5][6][7][8][9][10] ITN durability assessments and evaluations must be conducted under various conditions and settings. To address these issues, the World Health Organization released its Guidelines for Laboratory and Field Testing of Long-Lasting Insecticidal Nets in November 2005 6 and Guidelines for Monitoring the Durability of Long-Lasting Insecticidal Mosquito Nets in 2010.…”
Section: Introductionmentioning
confidence: 99%